(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
High amplitude wave wake due to water flow on a school boat hull can prejudice directly residents of riverside communities by inducing erosions, damage to fixed or floating structures and also, damage to smaller boats, fishermen and swimmers. Therefore, designers introduced wave deflector surfaces in a new fleet of school boats to reduce the amplitude of the boat wave wake. In this study, the applicability of these surfaces were evaluated using computational tools. Initially, a multiphasic computational model of a Wigley hull was created in order to validate the numerical model. The validation model had good accordance compared to experimental results, with errors below 7% for resistance coefficient. Later, the school boat model was compared with images from the real operating school boat, where similarities between the two were observed. Models with different operation points were created. Finally, the comparison with, and without the wave deflector surfaces made it possible to notice the wave amplitude reduction. The wave deflector showed a efficiency improvement for velocities from 17.5 up to 20 km/h, above the usual operation speed of 15 km/h, which makes your use unfavorable. The methodology adopted was consistent and it can be used for a large range of investigations of this type.